Costs in the Norwegian Payment System: Questionnaires - Olaf Gresvik; Harald Haare (Norges Bank, 2009)
In this memo, questionnaires for the study: "Costs in the Norwegian payment system" are shown. The study included three surveys, towards Merchants, Households and Banks.
hdl:11250/2507917
Keywords: D12; D23; D24; 330; cash payments; card payments; giro payments; social costs; private costs; unit costs; banks' efficiency